2017
DOI: 10.1007/s12272-017-0979-x
|View full text |Cite
|
Sign up to set email alerts
|

The combination of curcumin and 5-fluorouracil in cancer therapy

Abstract: 5-Fluorouracil (5-FU) alone or in combination with other therapeutic drugs has been widely used for clinical treatment of various cancers. However, 5-FU-based chemotherapy has limited anticancer efficacy in clinic due to multidrug resistance and dose-limiting cytotoxicity. Some molecules and genes in cancer cells, such as nuclear factor kappa B, insulin-like growth factor-1 receptor, epidermal growth factor receptor, cyclooxygenase-2, signal transducer and activator of transcription 3, phosphatase and tensin h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
56
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 94 publications
(64 citation statements)
references
References 139 publications
3
56
0
2
Order By: Relevance
“…Although 5-FU itself induces NF-κB, curcumin through suppression of NF-κB and antiapoptosis genes including Bcl-xL has a synergic effect via reduction of chemoresistance (Shakibaei et al, 2013;Shakibaei et al, 2015). Similar results have shown a synergistic effect on NF-κB inhibition by curcumin and 5-FU on other cancer cell types such as esophageal squamous cell carcinoma (Tian, Fan, Zhang, Jiang, & Zhang, 2012;Wei, Yang, Cao, & Zhao, 2018). Curcumin via activation of IκB reduces NF-κB activity in ovarian cancer cell lines, leading to potentiation of apoptosis induction by cisplatin (Fogoros, Choi, & Liu, 2005).…”
Section: Inhibition Of Nf-κbmentioning
confidence: 77%
“…Although 5-FU itself induces NF-κB, curcumin through suppression of NF-κB and antiapoptosis genes including Bcl-xL has a synergic effect via reduction of chemoresistance (Shakibaei et al, 2013;Shakibaei et al, 2015). Similar results have shown a synergistic effect on NF-κB inhibition by curcumin and 5-FU on other cancer cell types such as esophageal squamous cell carcinoma (Tian, Fan, Zhang, Jiang, & Zhang, 2012;Wei, Yang, Cao, & Zhao, 2018). Curcumin via activation of IκB reduces NF-κB activity in ovarian cancer cell lines, leading to potentiation of apoptosis induction by cisplatin (Fogoros, Choi, & Liu, 2005).…”
Section: Inhibition Of Nf-κbmentioning
confidence: 77%
“…27,28 However, 5-FU-based therapeutic has limited clinical treatment because of dose-limiting cytotoxicity. 29 Our study still contains certain limitations. Although we discovered the potential diagnostic value of UPP1 in thyroid cancer and related EMT, the specific mechanisms of UPP1 in thyroid cancer remain to be further investigated.…”
Section: Discussionmentioning
confidence: 90%
“…Yu et al found that the growth of SMMC-7721 cells could be resisted by CU, which was due to inhibiting the Bcl-2 and activate Bax protein and promote caspase 3 pathway [36]. And some researches also demonstrated that the anticancer effect of 5-FU against cancers could be enhanced by CU via down-regulation of COX-2 and NF-κB pathways [37,38]. Therefore, it may be an ideal strategy to use the combination of CU and 5-FU to treat HCC.…”
Section: Discussionmentioning
confidence: 99%